ANALISA REOLOGI DASAR ASPAL MODIFIKASI NANO ABU CANGKANG SAWIT - Fitra Ramdhani; Bambang Sugeng Subagio; Harmein Rahman; Russ Bona Frazila (Racic : Rab Construction Research, 2023)
The development of asphalt modification using nano technology is one of the innovations in creating a new material that is nano meter scale that has a superior nature of large material. The uniqueness of the material nano is the smaller the size of the material, the surface area and performance of the material characteristics in the asphalt mixture are increasing. This study aims to determine the effect of the addition of nano ash of palm shells (NACS) on bitumen on the nature of the basic rheology of asphalt. Research methods use testing methods in the laboratory. The nano material used is a palm shell ash material obtained from the residual waste of the burning of the palm shell originating from Riau which is then processed into nano ash of the palm shell (NACS) in the ITB Chemical Laboratory. The asphalt used is asphalt Pen 60/70 Pertamina production. The use of NACS material in asphalt modification with variations of 1%, 2%, and 3%NACS can reduce penetration values, increase soft points, reduce ductility values and reduce mixing temperatures and compaction temperatures in line with increasing percentage of NACS .. Keywords: Nano Palm Shell Ash (NACS), Basic Asphalt Rheology,Nano Technology ​